Historic Developments, Current Technologies and Potential of Nanotechnology to Develop Next Generation Solar Cells with Improved Efficiency - Nisith Raval; Ajay Kumar Gupta (Center of Biomass & Renewable Energy (CBIORE), 2015)
Sun is the continuous source of renewable energy, from where we can get abundant of solar energy. Concept of conversionof solar energy into heat was used back in 200 B.C. since then, the solar cells have been developed which can convert solar energy into theelectrical energy and these systems have been produced commercially. The technologies to enhance the power conversion efficiency (PCE)have been continuously improved. Different technologies used for developing solar cells can be categorized either on the basis of materialused or techniques of technology development which is further termed as ‘first generation’ (e.g. crystalline silicon), ‘second generation’(thin films of Amorphous silicon, Copper indium gallium selenide, Cadmium telluride), ‘Third generation’ (Concentrated, Organic and Dyesensitize solar cell). These technologies give PCE up to 25% depending on the technology and the materials used. Nanotechnology enablesthe use of nanomaterial whose size is below 100 nm with extraordinary properties which has the capability to enhance the PCE to greaterextent. Various nanomaterials like Quantum Dots, Quantum well, carbon nanotubes, Nanowire and graphene have been used to makeefficient and economical solar cells, which not only provide high conversion efficiency economically but also are easy to produce. Today,by using nanotechnology, conversion efficiency up to 44.7 % has been achieved by Fraunhofer Institute at Germany. In this review article,we have reviewed the literature including various patents and publications, summarized the history of solar cell development, developmentof different technologies and rationale of their development highlighting the advantages and challenges involved in their development forcommercial purpose. We have also included the recent developments in solar cell research where different nanomaterials have beendesigned and used successfully to prove their superiority over conventional systems.